How does solar energy transform landscapes? A comparative spatial analysis of 46 built solar power plants in the Netherlands - Becker, Florian; Oudes, Dirk; Stremke, Sven (Renewable energy, 2025)
The growing number of solar power plants (SPP) is transforming landscapes worldwide. This transformation leads to societal concerns regarding land use competition, biodiversity loss, and landscape experience, leading to local opposition. Two kinds of spatial measures can address aforementioned societal concerns: alterations of the photovoltaic system and adding landscape elements. Existing research mainly focused on single societal concerns or lacks substantial empirical case evidence. This study provides an overview of and critically assesses the range and extent of spatial measures that materialise in built SPPs, based on the sample of 46 SPPs in the Netherlands. The spatial analysis resulted in the identification of 43 types of spatial measures, each one addressing at least one societal concern. Several measures were identified to have synergies amongst each other. Trade-offs between spatial measures were identified in combination with specific site characteristics. This study confirms the potential of spatial measures to address societal concerns in SPPs. However, the large sample of SPPs reveals that efforts like planting vegetation, identified in many cases, are counterbalanced by the removal of extensive vegetation structures in other cases. The identification of synergies and trade-offs can inform policy-makers, local authorities and SPP developers to advance future SPP developments. •First comparative case study of spatial measures in 46 Dutch Solar Power Plants.•Studied measures address land use competition, biodiversity, and landscape experience.•Total of 43 types of measures were identified addressing particular societal concerns.•The doubling of photovoltaic system density in the past years impedes multifunctionality.•The ecological impact of SPP development depends on the previous land use of the site.